Transparent exopolymer particles (TEP) and their potential effect on membrane biofouling - Meng, Shujuan (2013)
Transparent exopolymer particles (TEP) have been described as a class of particulate acidic polysaccharides, which are large, transparent organic particles, and commonly found in seawater, surface water, and wastewater. Due to their unique physicochemical characteristics, more and more attention has recently been given to the effects of TEP on membrane fouling. In this review, the characteristics and determination methods of TEP as well as its potential effect on membrane biofouling are discussed. It appears that the analytical methods for TEP available in the literature are still debatable, and there is room for further improvement. Nevertheless, evidence suggests that TEP might be involved in the development of membrane fouling, especially at the early stage of biofilm development on membranes.